Innovación en la gestión de procesos de las COAC del cantón La Maná, para crear nuevos productos o mejorar los existentes, año 2018. Caso específico COAC Cámara de Comercio. - Álvarez Espín, Jessica Catalina (2019)
The objective of this research was to evaluate innovation in the process management of savings and loan cooperatives in La Maná, to create new products or improve existing ones. For this purpose, the methods that were used: analytical, deductive and the types of bibliographic research by reviewing existing information in relation to process management. Through diagnostic research and field research, data and information was obtained from primary sources through the application of interviews directed to 12 administrative and surveys to 398 members, whose results allowed to know that there was a high level of ignorance about the management of processes. The description of the financial services portfolio revealed that the CACPECO, Futuro Lamanense and Virgen del Cisne SALC had a broad portfolio of services; while the SALCs: Andina, Coorcotopaxi, Occidental, Sierra Center, Sumak Kawsay Cámara de Comercio and Sinchi Runa evidenced a smaller portfolio of services focused on capturing savings, credits and non-financial services as facilitation collection centers. Through the value chain it was possible to demonstrate that the processes that give value to the SALC are the capture of Savings and the Placement of Loans. For this reason, the insertion of the following innovations was suggested: Savings Account "Peques", "My House" programmed savings and in Loan Placements services such as: Emerging loan, the issuance of debit cards and ATMs for credit cards. organizations that presented a level of deficient services, which will give more value, allowing to implement new processes that challenge to raise the level of quality and continuous improvement; It is also important to highlight that these strategies can be incorporated even by those entities that presented a wide portfolio of services as an added value that will allow to achieve an innovation of the existing products.